The new atheist novel : fiction, philosophy and polemic after 9/11 - Bradley, Arthur (New directions in religion and literature., 2010)
'The New Atheist Novel' is a study of a major new genre of contemporary fiction. It examines how Richard Dawkins's so-called 'New Athemism' movement has caught the imagination of four eminent modern novelists: Ian McEwan, Martin Amis, Salman Rushdie and Philip Pullman.